2018
DOI: 10.3390/nu10060728
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Exposure to High Sucrose Levels near Weaning Has a Similar Long-Lasting Effect on Hypertension as a Long-Term Exposure in Rats

Abstract: Adverse conditions during early developmental stages permanently modify the metabolic function of organisms through epigenetic changes. Exposure to high sugar diets during gestation and/or lactation affects susceptibility to metabolic syndrome or hypertension in adulthood. The effect of a high sugar diet for shorter time lapses remains unclear. Here we studied the effect of short-term sucrose ingestion near weaning (postnatal days 12 and 28) (STS) and its effect after long-term ingestion, for a period of seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 97 publications
(119 reference statements)
1
38
0
Order By: Relevance
“…In the present study, we found that eNOS expression decreased in the experimental groups that received sucrose for a short-and long-term period. This result is in agreement with findings presented in another paper from our group [2]. Several authors have reported that increases in SIRT1 expression are directly related to the expression and activity of eNOS; however, SIRT1 expression was only increased in the MS aortas in our experiments.…”
Section: Effects Of the Treatment With Rsv/qsc On Sirt 1 And Enos Expsupporting
confidence: 94%
See 4 more Smart Citations
“…In the present study, we found that eNOS expression decreased in the experimental groups that received sucrose for a short-and long-term period. This result is in agreement with findings presented in another paper from our group [2]. Several authors have reported that increases in SIRT1 expression are directly related to the expression and activity of eNOS; however, SIRT1 expression was only increased in the MS aortas in our experiments.…”
Section: Effects Of the Treatment With Rsv/qsc On Sirt 1 And Enos Expsupporting
confidence: 94%
“…The blood pressure was increased in both the SSP and MS rats. Hypertension in these groups had already been reported [2,3]. The increase in blood pressure was reversed by the RSV/QSC treatment and the blood pressure decreased in 17% in the SSP group and 11% in the MS group.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations